Impact of the pathogenetic type of postmenopause on the occurrence of tumors of the female reproductive system - L. A. Ashrafyan; I. B. Antonova; N. A. Babayeva; S. V. Ivashina; T. A. Motskobili; A. A. Myagkova (ABV-press, 2014)
The study included patients observed and treated in Russian scientific centre of roentgenradiology Ministry of Health Russian Federation in the period from 1999 to 2010 (n = 405): including 111 postmenopausal women who are without anamnestic data on the presence of cancer at any site, and the group of patients with gynecological cancer in postmenopause in including 60 patients with endometrial cancer, 67 patients with malignant epithelial ovarian tumors, 87 observations of cervical cancer and 80 patients with vulva cancer. The average age of the patients was 58.6 ± 0.4 years. The study of bone mineral density, body mass index and the level of estrogen receptor localization in different cancers of the reproductive system. Formed by 4 different types of menopause that best reflects a combination of hormone and hormone receptor status. This separation makes it possible to plan more differentiated the hormone replacement therapy in postmenopause. Along with this, there is reasonable prospects for prevention and early diagnosis of hormone-dependent tumors of the female reproductive system.